'They say God punishes people with HIV': experiences of stigma and discrimination among adults with HIV in Dili, Timor-Leste. Issue 10 (3rd October 2017) - Williams, Kate; Haire, Bridget G.; Nathan, Sally
Abstract: Little is known about the experiences of people with HIV in the small island nation of Timor-Leste. This study explored the HIV-related stigma experiences of adults aged between 18 and 40 living with HIV in Dili, Timor-Leste. Participants were interviewed on topics related to living with HIV, both as key informants describing the experience of others with HIV known to them, and also with respect to their own personal experiences. Findings suggest that people with HIV in Timor-Leste face stigma and discrimination in various contexts. In this predominantly Catholic country, perceptions of HIV and attitudes towards people with HIV appear to be commonly shaped by religious beliefs. In families and communities, participants encountered gossip, social exclusion and threats of violence. In health settings, participants experienced discrimination from health providers in the form of failing to maintain confidentiality and inappropriate treatment. The impact of stigma was profoundly negative and influenced participants' decision to disclose their status to others. Participants attributed stigma to a lack of information about HIV among the general public. Unless stigma reduction interventions also address the Church's role in shaping perceptions of HIV, education campaigns are unlikely to be effective in reducing HIV-related stigma.